Research-led curriculum development: pilot study on social studies - Imam, Syeda Rumnaz; Howlader, Vibekananda; Khatun, Marzina; Kalam, Md. Abul (BRAC Research and Evaluation Division (RED), 2020)
BRAC's EDU has been working to develop effective materials for it's learners from early on. In phase II the focus was on providing improved materials and refining curriculum to suit the needs of the learners. In the case of social studies it was decided to be activity based and would focus on developing the life skills of rural children (NFPE, 1999). This pilot study is an attempt to develop an assessment methodology for assessing what learners' know, can do and understand for achieving expected learning outcome, in order to evaluate the curriculum towards research-led curriculum development with special reference to knowledge, and understanding level of the learners of grade II. This is is a joint study of Research and Evaluation Division and Education Development Unit of BRAC.